HUBUNGAN NILAI KREATININ DENGAN TINGKAT KEPARAHAN PASIEN STROKE ISKEMIK BERDASARKAN NIHSS DI RUMAH SAKIT PUSAT OTAK NASIONAL JAKARTA - Barata Nur Aziiz (2023)
ABSTRACT Background: Stroke is the third highest cause of death in the world and has many complications. Stroke is classified into Ischemic and Hemorrhagic where ischemic stroke accounts for 87% of the total cases. Stroke complications involve many organ systems including the kidneys. Kidney function is important to prevent the development of secondary complications of stroke. Kidney damage can be assessed from creatinine levels in urine or blood. The National Institutes of Health Stroke Scale (NIHSS) is used to measure the severity of stroke which is valid and highly recommended. This study aims to determine the relationship between creatinine levels and the severity of ischemic stroke. Methods: This study use a cross-sectional design conducted in January-December at the Pusat Otak Nasional Prof. Dr. dr. Mahar Mardjono Hospital, East Jakarta. Sampling was carried out using a total sampling technique of 88 samples through medical records. Results: The severity of ischemic stroke using the NIHSS score showed 19 patients (21.6%) had a mild score, 53 patients (60.2%) had a moderate score, and 16 patients (18.2%) had a severe score. 40 patients (25.5%) had high creatinine levels. Chi-square test showed [P=0.023]. Conclusion: There is a relationship between increased creatinine levels and the NIHSS score in ischemic stroke patients at Pusat Otak Nasional Prof. Dr. dr. Mahar Marjono Hospital Jakarta. Keywords: Creatinine levels, Ischemic Stroke, NIHSS